Outcomes of endovascular thrombectomy in the elderly: a 'real-world' multicenter study. (2nd November 2018) - Alawieh, Ali; Starke, Robert M; Chatterjee, Arindam Rano; Turk, Aquilla; De Leacy, Reade; Rai, Ansaar T; Fargen, Kyle; Kan, Peter; Singh, Jasmeet; Vilella, Lukas; Nascimento, Fábio A; Dumont, Travis M; et al.
Abstract : Background: The efficacy of endovascular thrombectomy (ET) for acute ischemic stroke (AIS) in octogenarians is still controversial. Objective: To evaluate, using a large multicenter cohort of patients, outcomes after ET in octogenarians compared with younger patients. Methods: Data from prospectively maintained databases of patients undergoing ET for AIS at seven US-based comprehensive stroke centers between January 2013 and January 2018 were reviewed. Demographic, procedural, and outcome variables were collected. Outcomes included 90-day modified Rankin Scale (mRS) score, postprocedural National Institutes of Health Stroke Scale score, postprocedural hemorrhage, and mortality. Univariate and multivariate analyses were performed to assess the independent effect of age ≥80 on outcome measures. Subgroup analyses were also performed based on location of stroke, success of recanalization, or ET technique used. Results: Rates of functional independence (mRS score 0–2) after ET in elderly patients were significantly lower than for younger counterparts. Age ≥80 was independently associated with increased mortality and poor outcome. Age ≥80 showed an independent negative prognostic effect on outcome even when patients were divided according to thrombectomy technique, location of stroke, or success of recanalization. Age ≥80 independently predicted higher rate of postprocedural hemorrhage, but not success of recanalization. Baseline deficit and number of reperfusion attempts, but not Thrombolysis in Cerebral Infarction score were associated with lower odds of good outcome. Conclusion: The large effect size of ET on AIS outcomes is significantly diminished in the elderly population when using comparable selection criteria to those used in younger counterparts. This raises concerns about the risk–benefit ratio and the cost-effectiveness of performing this procedure in the elderly before optimizing patient selection.